Basic Local Alignment Search Tool - Bedell, Joseph (O'Reilly, 2011)
BLAST (Basic Local Alignment Search Tool) is a set of similarity search programs that explore all of the available sequence databases for protein or DNA. BLAST is the only book completely devoted to this popular and important technology and offers biologists, computational biology students, and bioinformatics professionals a clear understanding of this program. This book shows you how to get specific answers with BLAST and how to use the software to interpret results. If you have an interest in sequence analysis this is a book you should own.